Clear cell carcinomas of the ovary and kidney: clarity through genomics. Issue 5 (23rd February 2018) - Ji, Jennifer X; Wang, Yi Kan; Cochrane, Dawn R; Huntsman, David G
Abstract: Clear cell ovarian carcinoma (CCOC) and clear cell renal cell carcinoma (ccRCC) both feature clear cytoplasm, owing to the accumulation of cytoplasmic glycogen. Genomic studies have demonstrated several mutational similarities between these two diseases, including frequent alterations in the chromatin remodelling SWI–SNF and cellular proliferation phosphoinositide 3‐kinase–mammalian target of rapamycin pathways, as well as a shared hypoxia‐like mRNA expression signature. Although many targeted treatment options have been approved for advanced‐stage ccRCC, CCOC patients are still treated with conventional platinum and taxane chemotherapy, to which they are resistant. To determine the extent of similarity between these malignancies, we performed unsupervised clustering of mRNA expression data from these cancers. This review highlights the similarities and differences between these two clear cell carcinomas to facilitate knowledge translation within future research efforts. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.